Exploring the challenges of preparing an integrated report: a case study in the South African eco-tourism industry - McLeish, Mary-Anne (My University, 2016)
In recent years, the call for companies to account for their activities to a wide group of stakeholders has grown. Integrated reporting provides a platform for such stakeholder communication. Recent studies have, however, concluded that integrated reporting is viewed merely as an exercise to be undertaken to ensure compliance. This thesis explores the challenges faced by those charged with the preparation of the integrated report in the South African eco-tourism industry. It adopts a social constructivist ontology and is grounded in an interpretive epistemology. The eco-tourism industry is particularly suited to this study as the notion of sustainability and, more recently, integrated reporting is of great importance in a rapidly growing industry which places significant reliance on natural resources. It is required to deliver economic profits whilst ensuring that the differing needs of a range of stakeholders are met. A theoretical framework of change implementation, based on different mechanisms presented by existing literature, was developed and used in exploring the challenges encountered by a case organisation when preparing its integrated report. A qualitative case study was undertaken in which the role-players in the preparation of the integrated report of the case entity were interviewed, and the minutes of internal meetings and workshops and an external assurance report were reviewed. In this context, this thesis provides further understanding of the challenges faced by organisations in the preparation of an integrated report, providing insight into how preparers are interpreting and applying the guidelines found in the integrated reporting frameworks and codes on corporate governance.
In partial fulfilment of the requirements for the degree of: Masters of Commerce University of the Witwatersrand
Keywords: Corporate governance--South Africa; Corporation reports--South Africa; Sustainable development reporting--South Africa; Eco-tourism--South Africa